Corrigendum to “A mechanistic study of the temperature dependence of the stress corrosion crack growth rate in SUS316 stainless steels exposed to pressurized water reactor primary water” [Acta Mater. 114 (2016) 15–24] - Meisnar, M; Vilalta-Clemente, A; Moody, M; Wilkinson, A; Arioka, K; Lozano-Perez, S (Elsevier, 2016)
The authors regret that one of the main contributors to this paper was unintentionally omitted from the author list in the final version of the manuscript. The complete author list should read: Martina Meisnara, Arantxa Vilalta-Clementea, Michael Moodya, Angus J. Wilkinsona, Koji Ariokab, Sergio Lozano-Pereza,∗ The authors would like to apologise for any inconvenience caused.